Effect Of Sme’s E-Readiness and Online Food Delivery Apps Adoption Toward Business Performance - Reyna Nadhya Ulhaq; Jono Mintarto Munandarr; Amzul Rifin (Journal Research of Social Science, Economics, and Management, 2022)
Malaysia and Indonesia, in this case, have several similarities including the non-optimal performance of SMEs and the potential of online food delivery to improve SME performance. Stated that one of the most important factors in influencing the impact of e-commerce-adoption was readiness. The purpose of this study was to understand and compare e-readiness factors that influence online food delivery apps adoption and to understand the effects of online food delivery apps adoption on SME's performance between Malaysia and Indonesia. The number of samples used in this study amounted to 70 respondents. Research using SEM PLS as a data processing tool. The findings showed that the factors that influence the level of e-commerce-adoption in Indonesia are commitment, market forces, supporting industries e-readiness, and online food delivery apps adoption while in Malaysia only market forces has a significant effect on online food delivery apps adoption. In both countries, online food delivery apps adoption is positively and significantly influential to SME’s performance with a relatively equal significance value